Sexual development and menstrual function in adolescent girls after viral hepatitis - E. F. Chaykivska; T. F. Tatarchuk; О. V. Zanko; N. F. Zakharenko; N. K. Silina (Publishing House TRILIST, 2020)
Purpose of the study: to prove the pathological effect of chronic viral hepatitis on sexual development (SD) and menstrual function of adolescent girls by analyzing the secondary sexual characteristics and to determine the features of disorders of menstrual function (DMF)  in such patients. Materials and methods. The study involved 150 girls of pubertal age (12-17 years) who were divided into groups: the main group (n = 50) - patients with DMF and SD on the basis of chronic viral hepatitis B and C; comparison group (n = 50) - patients with DMF and SD on the basis of hepatobiliary system diseases (cholecystitis, dyskinesia of the biliary tract); control group (n = 50) - almost healthy girls. All patients underwent clinical analysis of menstrual function, appearance and development of secondary sexual characteristics, clinically determined the degree of SD and SD score calculated. Results. The whole spectrum of DMF in the main and comparison group was revealed. There were more patients with hypomenstrual type of DMF in the main group than in the comparison group: 37 (74%) against 28 (56%) (p <0.05). Patients with juvenile uterine bleedings were almost equally: 8 (16%) in the main and 7 (14%) in the comparison group (p <0.05). There were three times more patients with dysmenorrhea in the comparison group - 15 (30%) girls against 5 (10%) in the main group (p <0.05). The dependence of SD disorders and clinical form of DMF on the time of hepatitis development in the main group was revealed: SD delay and primary amenorrhea were more often with the disease onset in childhood, persistent oligomenorrhea was formed in the prepubertal period, and juvenile uterine bleedings and secondary amenorrhea in the late puberty (p <0.05). Conclusions. This study demonstrated the role of hepatobiliary system diseases in slowing puberty of girls, characterized by disturbance of the secondary sexual characteristics onset, deviation of the SD score. Dependence of DMF on periods of exacerbation of hepatobiliary system diseases was also determined.